2020
DOI: 10.1038/s41398-020-0852-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of social cognition skills and social determinants of health in predicting symptoms of mental illness

Abstract: Social factors, such as social cognition skills (SCS) and social determinants of health (SDH), may be vital for mental health, even when compared with classical psycho-physical predictors (demographic, physical, psychiatric, and cognitive factors). Although major risk factors for psychiatric disorders have been previously assessed, the relative weight of SCS and SDH in relation to classical psycho-physical predictors in predicting symptoms of mental disorders remains largely unknown. In this study, we implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 62 publications
2
27
0
5
Order By: Relevance
“…Previous studies have discussed the potential problems associated with the use of self-reports to track past events. 9 , 100 However, other reports have shown the relevance of tracing retrospective risk factors related to mental health outcomes, 101 social determinants of health, 102 , 103 and risk factors related to violence. 20 , 25 Our results revealed that the life stage in which social-contextual factors occurred was relevant to improving the computational predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have discussed the potential problems associated with the use of self-reports to track past events. 9 , 100 However, other reports have shown the relevance of tracing retrospective risk factors related to mental health outcomes, 101 social determinants of health, 102 , 103 and risk factors related to violence. 20 , 25 Our results revealed that the life stage in which social-contextual factors occurred was relevant to improving the computational predictions.…”
Section: Discussionmentioning
confidence: 99%
“…We developed a new instrument to systematically assess SES and SDH. This UCSF-ReDLat questionnaire has been culturally adapted with input from each enrolling site, based on previous reports as well as national censuses from Colombia, Brazil, Chile, and Perú and following cross-cultural implementation recommendations ( 59 – 64 ). The questionnaire captures educational attainment, race and ethnicity, health literacy, financial strain, food insecurity, housing insecurity, childhood trauma, social connections, social isolation, access to healthcare, occupation, and employment status.…”
Section: Redlat Ongoing Progress and Extensionsmentioning
confidence: 99%
“…Social capital can be understood as an inherent cohesive force that enables collective action within populations. With regards to mental disorders, social capital may lower risk while increasing intellectual cross-pollination, resilience capacity, successful adaptation, emotional intelligence, cooperation, and recovery [24,30,31]. Interventions to enhance social capital may be a cost-effective way of preventing and ameliorating mental health conditions while augmenting social and brain capital; sample interventions include community engagement and educative programs, and evidence-based forms of psychological treatment (e.g., cognitive processing therapy and sociotherapy for trauma survivors) [24].…”
Section: Foundational Disciplines Informing the Development Of Brain mentioning
confidence: 99%